EDUKASI PEMBUATAN JAMU YANG BAIK DAN AMAN PADA KELOMPOK JAMU GENDONG DI KOTA BENGKULU - Suci Rahmawati; Nori Wirahmi; Camelia Dwi Putri Masrijal; Rose Intan Permasari; Oky Hermansyah; Samwilson Slamet (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Usaha Jamu Gendong (UJG) is a herbal medicine business carried out by individuals using traditional medicine ingredients in the form of fresh liquid to be sold directly to consumers. This service activity was aimed to increasing knowledge and providing skills on how to make good and safe jamu for UJG group in Bengkulu City. This activity was carried out on October 22, 2022 with 20 participants. This service activity is carried out using discussion and demonstration methods. Evaluation of activities is carried out by giving questionnaire sheets given before and after the activity. The results of the questionnaire evaluation obtained that the average score of 20 participants before and after the activity was 90.6 and 99.2, respectively. From the implementation of the activities, it can be concluded that there is an increase in the knowledge of the herbal medicine group regarding how to make good and safe traditional medicines.